PENGEMBANGAN INFOGRAFIS SEBAGAI MEDIA PENUNJANG PEMBELAJARAN P5 DI KELAS VIII A SMP NEGERI I BANTAENG - Andi Meisya Nurul Maulidiah; ABD Haling; Andromeda Valentino Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to develop infographics as an innovative learning media in the subject of Pancasila Education and Strengthening the Pancasila Student Profile (P5) with the topic “Voice of Democracy” at the Junior High School (SMP) level. The development method used is the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, student needs and learning constraints were identified through surveys and interviews with teachers and students. The infographics developed were tested on students of class VIII A SMP Negeri 1 Bantaeng. The effectiveness of the media was measured using pre-test, post-test, and student response questionnaires to the infographics. The results showed that the use of infographics improved students' conceptual understanding in the very good category, and encouraged creativity and participation in class discussions. Based on the evaluation, the infographics were rated excellent from the aspects of design, content, and usability by teachers and students. Thus, this infographic is recommended as a supporting media for P5 learning.